Direct power control of a grid-connected photovoltaic system using a fuzzy-logic based controller. (March 2017) - Farahani, Hassan Feshki; Rashidi, Farzan
In this paper a fuzzy logic-based controller is proposed for direct power control of three-phase grid-connected photovoltaic (PV) inverters. To demonstrate the effectiveness of the control method, a typical grid-connected PV inverter is implemented and the performance of the proposed technique is compared to a traditional proportional–integral (PI) controller. Numerical simulation results illustrate that the proposed fuzzy controller performs well in independently regulating the active and reactive output powers. Moreover, comparisons of simulation results between fuzzy and PI controllers show advantages of the fuzzy-based technique in terms of transient response characteristics, such as fast response, small overshoot, acceptable steady-state fluctuation, and high robustness.